Analisis Hubungan Kompensasi, Motivasi dan Lingkungan Kerja dengan Kinerja Karyawan pada Lembaga Bantuan Hukum Padang - Marvita Yenti Syafrida anggaraini; Gustati Gustati; Fera Sriyunianti (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2024)
This study aims to analyze how the relationship between compensation, motivation and work environment with employee performance at the Lembaga Bantuan Hukum Padang. This study uses a mixed method with quantitative and qualitative analysis (Sequential Explanatory). This method combines quantitative and qualitative research methods sequentially, where in the first stage the research was carried out with quantitative methods to collect quantitative data using questionnaires, then in the second stage the research used qualitative methods to prove and strengthen the quantitative data that had been obtained in the first stage. The results of this study indicate that the compensation variable with a TCR of 80.0% in the good category, the motivation variable with a TCR of 83.5% in the good category, the work environment variable with a TCR of 69.8% in the good category and the employee performance variable with a TCR of 85. .0% in the very good category. The correlation in this study shows that compensation has a moderate and insignificant relationship with employee performance, motivation has a strong and significant relationship with employee performance, and the work environment has a strong and positive relationship with employee performance. This quantitative data is supported by the results of interviews with several employees at the Lembaga Bantuan Hukum Padang. Keywords: Kompensasi, Motivasi, Lingkungan Kerja, dan Kinerja Karyawan.